2017
DOI: 10.1016/j.anai.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic CD4 lymphocytopenia

Abstract: Background Idiopathic CD4 lymphocytopenia (ICL) is a rare condition characterized by an unexplained deficit of circulating CD4 T cells leading to increased risk of serious opportunistic infections. The pathogenesis, etiology, clinical presentation, and best treatment options remain unclear. Objective To describe the clinical presentation, treatment strategies, and outcome of patients with ICL seen in a single referral center. Methods In a retrospective study, from January 1993 to January 2014, the demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…A compilation of various clinical and demographic features of ICL is in Table 1. 2,[5][6][7][8] The disease appears to present in the 4th decade with no definite sex preponderance. Opportunistic infections (OI) seem to be the most common presenting feature.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A compilation of various clinical and demographic features of ICL is in Table 1. 2,[5][6][7][8] The disease appears to present in the 4th decade with no definite sex preponderance. Opportunistic infections (OI) seem to be the most common presenting feature.…”
Section: Epidemiologymentioning
confidence: 99%
“…The symptoms varied and included pruritus, erythroderma, 42 vesicles, warts, verrucous papules and plaques, 79 condylomata, 80 and mycetoma (Exophiala jeanselmei and M. chelonae). 52 Infection of the skin included viral, bacterial, fungal and parasitic infections like herpes zoster, HPV, 80 molluscum contagiosum, 59 Stenotrophomonas maltophilia, 53 MAC, 51 Candida albicans, tinea corporis, 60 tinea pedis, 68 cryptococci, 8 Aureobasidium species, Alternaria species, and Hortaea werneckii, leishmaniasis. 49 Premalignant lesions (vulval intraepithelial neoplasia, Bowen disease) and malignancies (e.g., Kaposi sarcoma, 61 squamous cells carcinoma and basal cell carcinoma) have been reported.…”
Section: Infectionsmentioning
confidence: 99%
“…3), autoimmunity (4-6), and HPV-or EBV-related neoplasias (7,8) that in some cases can be fatal (9,10). Twenty-five years after the CDC defined ICL, its etiology remains elusive, and there is currently no efficacious treatment, other than the use of antibiotics for prophylaxis or treatment of opportunistic infections (11). Therefore, identifying the etiology/ ies of ICL is important not only to characterize the molecular and cellular mechanisms that can trigger and sustain CD4 lymphopenia in humans but also to direct possible therapeutic interventions in afflicted patients.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic infections are frequent in patients with ICL. In a retrospective study of 24 ICL patients, 71% were found to have opportunistic infections [50] . In a review of 258 ICL cases between 1989 and 2012, 87.6% of patients had opportunistic infections and they were most commonly caused by Cryptococcus species (26.6%).…”
Section: Discussionmentioning
confidence: 99%